2018
DOI: 10.2134/jeq2018.01.0015
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium Uptake by Ryegrass and Ryegrass–Clover Mixtures under Different Liming Rates

Abstract: Cadmium accumulates in soils that receive repeated applications of Cd‐rich superphosphate fertilizers. There is evidence that adding clovers to a crop solubilizes soil Cd, increasing the bioavailability of Cd. This can lead to high plant Cd concentrations. This research aimed to test whether liming‐induced increases in pH in mixed crops of clovers and ryegrasses reduced forage Cd concentrations. A greenhouse pot trial applied lime at three rates (0, 1, and 2% of soil dry weight) to eight different plant treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Thus, the effect of N application on Cd accumulation remains controversial [12]. In general, N fertilization often decreases soil pH, which increases the solubility and mobility of Cd in the soil [19,20]. Ji et al [12] also highlighted a more direct effect of N fertilization in Cd uptake by suggesting a mechanism in which the active uptake and influx rate of Cd 2+ into the roots of Italian ryegrass (Lolium multifolorum Lam.)…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the effect of N application on Cd accumulation remains controversial [12]. In general, N fertilization often decreases soil pH, which increases the solubility and mobility of Cd in the soil [19,20]. Ji et al [12] also highlighted a more direct effect of N fertilization in Cd uptake by suggesting a mechanism in which the active uptake and influx rate of Cd 2+ into the roots of Italian ryegrass (Lolium multifolorum Lam.)…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are also in line with the observations of Ashraf et al [64], who reported the important role of FYM in the phytoextraction of HMs by ryegrass in contaminated soil. The reduced HMs uptake and vigorous plant growth in the presence of FYM might be due to the acidification of the rhizosphere (due to the release of organic acids by the microbes in FYM) that causes higher nutrient availability to plants and subsequently improved plant growth [66]. Our findings indicate that the addition of FYM could be useful in reducing HMs uptake in grasses and enhancing phytoremediation and sustainable production of grasses under water-deficient conditions.…”
Section: Discussionmentioning
confidence: 78%
“…They are commonly found in wetland environments and suitable for wastewater treatment. Clover plants are known for fixing nitrogen in the soil, have a dense root system, and can stabilize cadmium [59]. Bamboo is a fast-growing plant with a high root density [60].…”
Section: Suitable Plant Selectionmentioning
confidence: 99%